Booze, Bars, and Bystander Behavior: People Who Consumed Alcohol Help Faster in the Presence of Others - van Bommel, Marco; van Prooijen, Jan-Willem; Elffers, Henk; Van Lange, Paul A. M. (Frontiers in Psychology, 2016)
People help each other less often and less quickly when bystanders are present. In this paper, we propose that alcohol consumption could attenuate or reverse this so-called bystander effect. Alcohol impairs people cognitively and perceptually, leading them to think less about the presence of others and behave less inhibited. Moreover, alcohol makes people more prone to see the benefits of helping and not the costs. To provide an initial test of these lines of reasoning, we invited visitors of bars in Amsterdam to join our study at a secluded spot at the bar. We manipulated bystander presence, and at the end of the study, we measured alcohol consumption. When participants took their seats, the experimenter dropped some items. We measured how many items were picked up and how quickly participants engaged in helping. Results revealed that alcohol did not influence the bystander effect in terms of the amount of help given. But importantly, it did influence the bystander effect in terms of response times: People who consumed alcohol actually came to aid faster in the presence of others.